2007
DOI: 10.1254/jphs.fp0070214
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Adenosine-Induced Responses in the Guinea-Pig Trachea During Long-Term Caffeine Treatment: Possible Role of Epithelium

Abstract: Abstract. The responses to adenosine were studied on isolated, methacholine-precontracted tracheal strips of guinea pigs in the course of long-term caffeine or solvent treatment. Guinea pigs were fed caffeine for 10 weeks (average serum caffeine concentration: 39.1 ± 3.9 µM). In epithelium-intact tracheal preparations (EITPs), sensititization to adenosine-induced relaxation (AIR) developed. It attained a maximum in week 1 of caffeine treatment, and then its level diminished and disappeared completely by weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Advenier et al (1988) suggested that epithelium had an influence on the mechanical response of guinea pig trachea to adenosine, but a later article (Thorne and Broadley, 2001) did not support this possibility. However, treatment with caffeine for 10 weeks led to changes in adenosine-induced relaxation that did seem to involve the epithelium (Brugós et al, 2007). Adenosine induced a cholinergic tracheal reflex contraction in guinea pig in vivo via an A 1 receptor-dependent mechanism (Reynolds et al, 2008).…”
Section: B Smooth Muscle and Its Innervationmentioning
confidence: 98%
“…Advenier et al (1988) suggested that epithelium had an influence on the mechanical response of guinea pig trachea to adenosine, but a later article (Thorne and Broadley, 2001) did not support this possibility. However, treatment with caffeine for 10 weeks led to changes in adenosine-induced relaxation that did seem to involve the epithelium (Brugós et al, 2007). Adenosine induced a cholinergic tracheal reflex contraction in guinea pig in vivo via an A 1 receptor-dependent mechanism (Reynolds et al, 2008).…”
Section: B Smooth Muscle and Its Innervationmentioning
confidence: 98%